Usungan Art Exhibition - Mohamad Faizuan, bin Mat (2019)
This exhibition is the outcomes of the study conducted on 21 - 25 November 2018 in Kabong, Sarawak regarding with a practice by Sarawak coastal community called Usungan. USUNGAN: The Presentation of Innovative and Artistic Creation in Bonded Community, Kabong is an exbihition of the colourful tradition of Usungan processions are a common feature during the year-end school holiday season in Sarawak coastal areas. Usungan refers to the beautifully sculptured carriages or palanquin in which the children are carried around the neighborhood with. The event was held to celebrate a large group of children who completed their studies in the Al- Quran recitals. It is unique practice or tradition and it is only existing in the Borneo Island. Especially, Sarawak coastal areas continue to maintain and preserve it. Through the very interesting design of the Usungan, the Malays people of Sarawak has proven to have created their creativity and innovation. The Usungan come in all kinds of subject-matter such as plane, helicopter, fish, birds, fruits, insects etc.